Effect of Myocardial Fibrosis on Left Ventricular Function in Rheumatic Mitral Stenosis: A Preliminary Study with Cardiac Magnetic Resonance - Elen, Elen; Atmadikoesoemah, Celly A.; Kasim, Manoefris (Indonesian Journal of Cardiology, 2017)
Background: Left ventricular (LV) dysfunction was frequently found in rheumatic mitral stenosis. Myocardial fibrosis had been revealed in rheumatic heart disease and could be associated with LV dysfunction. We evaluate myocardial fibrosis profile related to LV function in rheumatic mitral stenosis with cardiac magnetic resonance (CMR). Methods: Eighteen patients with severe rheumatic mitral stenosis without history of coronary artery disease or its risk factors underwent 1.5T CMR examination. LV ejection fraction (LVEF), right ventricular ejection fraction (RVEF), myocardial fibrotic tissue were evaluated with CMR. Other hemodynamic data was derived from echocardiography results. Results: These patients (40.4±10.5 years old, 72.2% female, 66.7% atrial fibrillation) had LVEF of 50.9±15.9% and RVEF of 37.7±13.9%. Volume of fibrotic tissue in these patients were 16.6 (5.5-55.8)%. In multivariate analysis, volume of fibrotic tissue was a significant predictor of LVEF that myocardial fibrotic tissue of 1% was associated with LVEF reduction of 0.87% (95% CI 0.51%-1.24%). Conclusion: LV function was determined by the extent of myocardial fibrosis in rheumatic mitral stenosis.   Abstrak Latar Belakang: Disfungsi ventrikel kiri (LV) sering ditemukan pada mitral stenosis rematik. Fibrosis miokardium ditemukan pada penyakit jantung rematik. Fibrosis miokardium pada penyakit jantung rematik juga dihubungkan dengan disfungsi LV. Kami mengevaluasi profil fibrosis miokardium yang berhubungan dengan fungsi LV pada mitral stenosis rematik dengan cardiac magnetic resonance (CMR). Metode: Dilakukan pemeriksaan 1.5T CMR pada delapanbelas pasien dengan mitral stenosis rematik berat tanpa riwayat penyakit jantung koroner atau faktor resikonya. Fraksi ejeksi LV (LVEF), fraksi ejeksi RV (RVEF), dan jaringan fibrotik miokardium dievaluasi menggunakan CMR. Data hemodinamik lainnya didapatkan dari pemeriksaan ekokardiografi. Hasil: Pasien tersebut (40.4±10.5 tahun, 72.2% perempuan, 66.7% fibrilasi atrium) memiliki LVEF 50.9±15.9% dan RVEF 37.7±13.9%. Volume jaringan fibrotic pada pasien tersebut adalah 16.6 (5.5-55.8)%. Dalam analisis multivariat, volume jaringan fibrotic adalah prediktor LVEF yang signifikan yaitu 1% jaringan fibrotic miokardium dihubungkan dengan menurunan LVEF sebesar 0.87% (95% CI 0.51%-1.24%). Kesimpulan: Fungsi LV dipengaruhi seberapa besar fibrosis miokardium pada mitral stenosis rematik